2014
DOI: 10.1007/s00438-014-0962-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression subtractive hybridization and comparative expression of a pore-forming toxin and glycosyl hydrolase genes in Rhizoctonia solani during potato sprout infection

Abstract: Rhizoctonia solani is a plant pathogenic fungus that causes black scurf on tubers and stem and stolon canker on underground parts of potato plant. Early in the season, the fungus attacks germinating sprouts underground before they emerge from the soil. Damage at this stage results in delayed emergence of weakened plants with poor and uneven stands. The mechanism underlying this phenomenon has been investigated in this study by coupling a cDNA-suppression subtractive hybridization (SSH) library to differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 91 publications
0
8
1
Order By: Relevance
“…It has been reported that similar proteins can be found in other pathogenic fungi and bacteria suggesting a potential role of these proteins in the virulence of these microorganisms [ 62 ]. Interestingly, it has been recently shown that when R. solani AG3 was co-cultured with the soil-inhabiting bacterial antagonist Bacillus subtilis and with the mycoparasite Stachybotrys elegans , RSENDO1 gene encoding a delta-endotoxin CytB gene was downregulated in contrast to the upregulation shown in our study [ 13 ]. A gene containing the ricin b-like lectin domain involved in the production of the highly toxic legume lectin ricin was also highly upregulated almost 16 times in both treatments.…”
Section: Discussioncontrasting
confidence: 81%
“…It has been reported that similar proteins can be found in other pathogenic fungi and bacteria suggesting a potential role of these proteins in the virulence of these microorganisms [ 62 ]. Interestingly, it has been recently shown that when R. solani AG3 was co-cultured with the soil-inhabiting bacterial antagonist Bacillus subtilis and with the mycoparasite Stachybotrys elegans , RSENDO1 gene encoding a delta-endotoxin CytB gene was downregulated in contrast to the upregulation shown in our study [ 13 ]. A gene containing the ricin b-like lectin domain involved in the production of the highly toxic legume lectin ricin was also highly upregulated almost 16 times in both treatments.…”
Section: Discussioncontrasting
confidence: 81%
“…The primers used in this study are listed in Additional file 12 : Table S7. Expression of genes was normalized by G3PDH expression [ 68 ] and relative expression values were calculated according to the 2 -∆∆Ct method [ 69 ]. Analysis of variance (ANOVA, one way) was conducted on gene expression and phenotypic data using a General Linear Model implemented in SPSS ver.…”
Section: Methodsmentioning
confidence: 99%
“…Recently a number of studies have used gene expression analysis to study specific aspects of R . solani biology, including during sclerotia formation [ 30 ], the response to antagonistic bacteria [ 31 ], and during infection of different hosts looking at the plant [ 15 ] or pathogen side [ 32 , 33 ] of the interaction. In this study we have investigated the interaction between wheat and R .…”
Section: Introductionmentioning
confidence: 99%